The Adaptive Helix Model as a Catalyst for the Growth of the Digital and Green Economies - Alnouman, Saleh (Global journal of Business and Integral Security, 2026)
This article introduces the Adaptive Helix Model (AHM) as a critical framework for advancing digital and green economies. Building on the evolution of helix models, AHM embeds adaptability across eight interconnected helices: Strategic Alignment, Governance Leadership, Venture Finance, Knowledge Dynamics, Economic Ecosystem, Techno-Ecosystems, Eco-Communication, and Society & Sustainability. The study identifies key challenges facing Innovation Zones and Ecosystems (IZEs), including financing, governance, industrial transformation, infrastructure disparities, labor dynamics, data security, and environmental pressures. It demonstrates how AHM provides structured pathways to address these challenges through agile governance, sustainable capital flows, talent development, ecosystem diversification, and resilient digital–physical infrastructure, complemented by transparent communication and inclusive adoption. Furthermore, the article argues that adaptivity is not only a theoretical advancement but also a practical necessity. It examines the potential challenges and risks associated with implementing AHM and suggests preventive and proactive strategies to ensure smooth, successful, effective, and growth-supporting implementation.